Tuning room temperature ferromagnetism of 'in-situ' inkjet printed Fe-doped ZnO films. (9th April 2019) - Fang, Mei; Li, Hao; Riazanova, Anastasia V; Rao, K V; Belova, Lyubov
Abstract: ZnO is a wide-band gap semiconductor widely used in optical and electric devices, associating with ferromagnetism at low dimension endowing its possibility for functional applications with magneto-optical and magneto-electric properties. We prepared ZnO and Fe-doped ZnO thin films ' in-situ ' on substrate by inkjet printing, and tuned the room temperature ferromagnetism (RTFM) of the film by Fe-doping concentration, film thickness and post annealing temperature. It was found that by Fe doping the saturation magnetization (MS ) of the film can be enhanced by more than 4 folds comparing with the un-doped film, i.e. from 0.9 emu g −1 for the ZnO film to 3.8 emu g −1 for the Fe-doped ZnO film with comparable thickness. The enhancement was attributed to the introduction of un-paired 3 d electrons which formed long range ferromagnetic ordering, as well as the consequent structure changes with smaller grains which increased the interface induced magnetism. By changing the annealing temperature and the film thickness, the defect-induced ferromagnetism was investigated. The RTFM shows thickness dependence with peak saturation magnetization value of 4.44 emu g −1 for the 45 nm thick film. The work provides an effective way of tuning magnetism in ZnO based films for functional device applications.